Preoperative Opioid Use in Knee Surgery Patients - Meredith, Sean J.; Nadarajah, Vidushan; Jauregui, Julio J.; Smuda, Michael P.; Medina, Shaun H.; Bennett, Craig H.; Packer, Jonathan D.; Henn, R. Frank, III (The Journal of Knee Surgery, 2019)
A cross-sectional analysis of data derived from patients undergoing knee surgery at a single institution was conducted. The objectives of the study were to determine the demographic, diagnostic, and psychologic factors associated with opioid use; and to determine the clinical correlates of opioid use. We hypothesized that preoperative opioid use would be associated with worse patient-reported outcome (PRO) measures. The sample consisted of 383 patients undergoing knee surgery. The patients were classified as either opioid or nonopioid users on the basis of medical record review. All participants completed a battery of clinical assessments, including the Patient-Reported Outcomes Measurement Information System computer adaptive testing in six domains: Physical Function, Pain Interference, Fatigue, Social Satisfaction, Anxiety, and Depression. Analyses were conducted to examine clinical variables as a function of opioid use. The results indicated that opioid use was associated with female gender, unemployment, smoking, higher American Society of Anesthesiologists scores, greater number of previous surgeries, depression or anxiety, and worse expectation of surgery (p < 0.05). Multivariable analysis found opioid use to be a significant independent predictor of multiple PRO measures in patients undergoing knee surgery. Potential explanations for these findings are presented, and clinical implications are discussed.
Keywords: opioid; knee; surgery; clinical characteristics; substance use